Genomic and Micro-Evolutionary Features of Mammalian 2 orthobornavirus (Variegated Squirrel Bornavirus 1, VSBV-1) - Dániel Cadar; Jonas Schmidt-Chanasit; Dennis Tappe (Microorganisms, 2021)
Mammalian 2 orthobornavirus (VSBV-1) is an emerging zoonotic pathogen discovered in several exotic squirrel species and associated with fatal human encephalitis. The dynamics of VSBV-1 spread and evolution in its presumed natural hosts are unknown. Here, we present the phylogeny, micro-evolution, cross-species transmission and spread of VSBV-1 at a temporal and spatial resolution within the limits of animal husbandry. The results showed that VSBV-1 can be classified into six distinct groups and that the most recent common ancestor of the known German strains emerged at least 20 years ago. We here demonstrate that the genetic diversity of the VSBV-1 groups is shaped primarily by in situ evolution and most of the amino acid changes are deleterious polymorphisms removed by purifying selection. Evidence of adaptive evolution has been found in the G and L genes which might have an influence on transmission fitness. Furthermore, there was also evidence for some form of adaptive changes in the glycoprotein which suggests that many sites might be subjected to positive pressure evolving under episodic directional selection, indicating past occurrence of positive selection. Host switching events were detected as dominant evolutionary mechanisms driving the virus-host associations. Virus spread by animal trade followed by subsequent local micro-evolution in zoos and holdings is responsible for diversifying strains. Time-resolved phylogeny indicated that Prevost’s squirrels might be the original squirrel species carrying and seeding the virus in Germany. This study provides the first insight into the ecology and micro-evolutionary dynamics of this novel viral pathogen in the captive exotic squirrel population under artificial ecological conditions (zoos and animal husbandry) and co-housing of different squirrel species.